Identification and characterization of a small sequence located at two sites on the amplifiable tetracycline resistance plasmid pAMalpha1 in Streptococcus faecalis. - Yagi, Y (1977)
Streptococcus faecalis DT-11 harbors the 6.0-megadalton plasmid pAMalpha1, which determines resistance to tetracycline (TC). When this strain is grown in the presence of TC for a number of generations, a reversible gene amplification occurs, generating tandem repeats of a 2.65-megadalton segment of the plasmid. On the basis of heteroduplex studies between various forms of pAMalpha1 and fragments generated by the Escherichia coli restriction endonuclease EcoRI, we have obtained direct evidence for the presence of a small sequence designated RS1 (for recombination sequence) located on both sides of the TC resistance determinant. Corresponding points on the two sequences are separated by 2.65 megadaltons of deoxyribonucleic acid. The two RS1 sequences have the same polarity and are of a size corresponding to about 380 nucleotide base pairs. The data presented serve as strong support for amplification models that are based on recombinational events involving the RS1 sequences.